The reception of the Deuteronomic social law in the primitive church of Jerusalem according to the Book of Acts - Friedl, A. (Acta Theologica, 2016)
The Book of Deuteronomy was extant in the Jewish cultural memory and played an important role in shaping Jewish identity. Its concept of the holy people of God, who live according to the social order given by YHWH and who stand in contrast to the pagan world, forms the social model for the Primitive Church in Jerusalem. Since New Testament exegesis has, to a large extent, neglected the role of this book of the Torah in understanding the Primitive Church, this study investigates the reception of Deuteronomy’s social law in Acts 2:42-47, 4:32-35, and 6:1-7, in terms of its theological or ecclesiological importance.